Detecting Anomalous Sensor Data In Wayside Diagnostics Using Enhanced LBP-Kurtograms - Kilinc, Onur; Vágner, Jakub (My University, 2017)
The research focuses on diagnosis of structural faults in railway vehicles which provides cost effective maintenance and safety. Hybrid sensor information is classified by the novel methodology; Enhanced LBP-Kurtograms which outperforms all others.
Detekce abnormálních signálů senzorů u traťové diagnostiky pomocí vylepšených LBP-kurtogramů
Keywords: wayside diagnosis; local binary patterns; wavelet packet energy; detecting abnormal data; traťová diagnostika vozidel; local binary patterns; wavelet packet energy; detekce abnormálních dat